Enhancing natural killer cell anti-tumour activity through macrophage manipulation - Palmer, Natasha; Khakoo, Salim; Sanchez-Elsner, Tilman; Vallejo, Andres F. (Frontiers in Immunology, 2025)
The tumour microenvironment (TME) is a complex and dynamic environment containing diverse cellular, stromal and soluble factors, that collectively influence cancer progression, immune evasion and therapeutic resistance. Among the immune components of the TME, macrophages and natural killer (NK) cells are key players, whose interactions, particularly their crosstalk, critically shape anti-tumour immunity. The macrophage–NK cell interplay can either promote or suppress immune responses depending on the context, representing both a challenge and a therapeutic opportunity. NK cells are key effectors capable of recognising and eliminating malignant cells without prior sensitisation, whereas macrophages exhibit remarkable plasticity, functioning as either promoters or suppressors of tumour immunity depending on their activation state. This review focuses on current strategies to harness macrophages in cancer therapy, including phenotype repolarisation, selective depletion, and disruption or enhancement of the macrophage-NK cell crosstalk to enhance NK cell-mediated tumour surveillance. Finally, we highlight emerging technologies, such as single-cell RNA sequencing, spatial transcriptomics, and proteomics, as powerful tools to elucidate the dynamic interplay between macrophages and NK cells and inform the next generation of immunotherapeutic interventions.